Management of Chronic and Neuropathic Pain with 10 kHz Spinal Cord Stimulation Technology: Summary of Findings from Preclinical and Clinical Studies - Tieppo Francio, Vinicius (Biomedicines, 2021)
Since the inception of spinal cord stimulation (SCS) in 1967, the technology has evolved dramatically with important advancements in waveforms and frequencies. One such advancement is Nevro’s Senza(®) SCS System for HF10, which received Food and Drug and Administration (FDA) approval in 2015. Low-frequency SCS works by activating large-diameter Aβ fibers in the lateral discriminatory pathway (pain location, intensity, quality) at the dorsal column (DC), creating paresthesia-based stimulation at lower-frequencies (30–120 Hz), high-amplitude (3.5–8.5 mA), and longer-duration/pulse-width (100–500 μs). In contrast, high-frequency 10 kHz SCS works with a proposed different mechanism of action that is paresthesia-free with programming at a frequency of 10,000 Hz, low amplitude (1–5 mA), and short-duration/pulse-width (30 μS). This stimulation pattern selectively activates inhibitory interneurons in the dorsal horn (DH) at low stimulation intensities, which do not activate the dorsal column fibers. This ostensibly leads to suppression of hyperexcitable wide dynamic range neurons (WDR), which are sensitized and hyperactive in chronic pain states. It has also been reported to act on the medial pathway (drives attention and pain perception), in addition to the lateral pathways. Other theories include a reversible depolarization blockade, desynchronization of neural signals, membrane integration, glial–neuronal interaction, and induced temporal summation. The body of clinical evidence regarding 10 kHz SCS treatment for chronic back pain and neuropathic pain continues to grow. There is high-quality evidence supporting its use in patients with persistent back and radicular pain, particularly after spinal surgery. High-frequency 10 kHz SCS studies have demonstrated robust statistically and clinically significant superiority in pain control, compared to paresthesia-based SCS, supported by level I clinical evidence. Yet, as the field continues to grow with the technological advancements of multiple waveforms and programming stimulation algorithms, we encourage further research to focus on the ability to modulate pain with precision and efficacy, as the field of neuromodulation continues to adapt to the modern healthcare era.